Impact of anatomic location on locally recurrent rectal cancer: superior outcome for intraluminal tumour recurrence - Klose, Johannes; Tarantino, Ignazio; Schmidt, Thomas; Bruckner, Thomas; Kulu, Yakup; Wagner, Jan Tobias; Schneider, Martin; Büchler, Markus W.; Ulrich, Alexis (Journal of gastrointestinal surgery, 2015)
Local recurrence of rectal cancer after curative surgery predicts patients’ prognosis. The correlation between the exact anatomic location of tumour recurrence and patients’ survival is still under debate. Thus, this study aimed to investigate the impact of the exact location of recurrent rectal cancer on post-operative morbidity and survival.